Unity Engine Sebagai Media Pengembangan Game Musik Cross Platform - Ramadhan, Muhammad Yakub; Rosnelly, Rika (U-NET Jurnal Teknik Informatika, 2023)
Majority of game developers only release their games for mainstream and well known platforms like Windows because of their huge user base which makes any other platforms like Linux can’t enjoy some new games only Windows users have. But with vast improvements in game development scene now a game developer can release a cross platform game with Unity Game Engine that supports many platforms including Linux. This research is conducted to develop an Unity cross platform game with rhythm game as the game genre which can be played with less demanding hardware and also taking part in improving players cognitive function.